O BRICS como fenômeno processual e dinâmico do ordenamento global: uma análise a partir de suas declarações de cúpulas - Freitas, William Daldegan de (2019)
The hypothesis defended here is that BRICS is a processual and dynamic phenomenon, adequate to the contemporary international order. As a processual phenomenon, it is understood that there is not a specific definition, much less the intention, regarding the format or the institutionalization to be achieved. It is a dynamic group, due to the perception of its members, which does not mean that there are limitations to their international strategies and initiatives. For this, the annual declarations of the BRICS summits, between 2009 and 2018, were analysed, through the historical methodology used in the analysis of documents and bibliography. The usage of software – AntConc e VOSviwer –, to count words and word association, enabled the construction of a textual analysis model and yielded results that prove the proposed hypothesis: the absence of formalization of the BRICS derives from the interest of its members, by preserving their independence and autonomy in the establishment of projects and policies, without harming their coordination as group. Moreover, the absence of formalization, above all, allows the creation of a bank and a reserve fund and fills the empty spaces, in a stimulus of the enlargement of the international order, without defying it